2017
DOI: 10.1097/wad.0000000000000208
|View full text |Cite
|
Sign up to set email alerts
|

Machine-learning Support to Individual Diagnosis of Mild Cognitive Impairment Using Multimodal MRI and Cognitive Assessments

Abstract: ReuseThis article is distributed under the terms of the Creative Commons Attribution (CC BY) licence. This licence allows you to distribute, remix, tweak, and build upon the work, even commercially, as long as you credit the authors for the original work. More information and the full terms of the licence here: https://creativecommons.org/licenses/ Takedown If you consider content in White Rose Research Online to be in breach of UK law, please notify us by emailing eprints@whiterose.ac.uk including the URL of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 42 publications
2
22
0
1
Order By: Relevance
“…Linear discriminant analysis (LDA) is another widely used classifier (Dai Z. et al, 2012 ; Cetin et al, 2016 ; De Marco et al, 2017 ; Qureshi et al, 2017a ; Wang et al, 2017 ), which projects features into a lower-dimensional space in which different groups of data can be maximally separately (Altman et al, 1994 ). LDA is a generalization of Fisher's linear discriminant and is based on the concept of searching for a linear combination of features that separate two groups (Mika et al, 1999 ).…”
Section: Classification or Prediction Strategiesmentioning
confidence: 99%
“…Linear discriminant analysis (LDA) is another widely used classifier (Dai Z. et al, 2012 ; Cetin et al, 2016 ; De Marco et al, 2017 ; Qureshi et al, 2017a ; Wang et al, 2017 ), which projects features into a lower-dimensional space in which different groups of data can be maximally separately (Altman et al, 1994 ). LDA is a generalization of Fisher's linear discriminant and is based on the concept of searching for a linear combination of features that separate two groups (Mika et al, 1999 ).…”
Section: Classification or Prediction Strategiesmentioning
confidence: 99%
“…With respect to dementia detection, multimodal approaches have been most effective in the medical imaging domain, where such methodologies have been used to combine information from various brain imaging technologies (Suk et al, 2014; Thung et al, 2017). For example, work from Beltrachini et al (2015) and De Marco et al (2017) has shown that the detection of MCI can be improved when combining features from MRI images with cognitive test scores in a multimodal machine learning classifier, compared to learning from either data source individually.…”
Section: Related Workmentioning
confidence: 99%
“…In fact, recent studies have also been show great promises for improving the accuracy of MCI identification by combining multiple structural and functional metrics, such as grey matter volume (GMV) and shortest path length (SPL). For example, Wee et al [ 18 ] first used both structural MRI and functional MRI data of each subject to construct multiple brain networks for each subject, and then extracted local clustering coefficient from each brain network of each subject as feature representation to perform the MCI identification task by using a multi-kernel learning algorithm; De Marco et al [ 19 ] used multiple machine learning models based on different metrics from both structural MRI and functional MRI data to investigate the performance of MCI identification; Tripathi et al [ 20 ] proposed an unsupervised framework for the classification of EMCI and LMCI by combining shape and voxel-based features from 12 brain regions; Jie et al [ 21 ] proposed a feature combination framework to combine both temporal and spatial features of dynamic functional networks to perform automatic identification of EMCI and LMCI. So far, although some results have been achieved for the identification of MCI subjects based on structural and functional MRI data, extracting which features and how to combine multiple features to improve MCI identification accuracy have always been a difficult problem.…”
Section: Introductionmentioning
confidence: 99%